Reading ancient folk literature The Omani story of “Abu Qahifa” is an example - Ahmed Siddig , Omar; Babikir Eltigani Siddig ,; Elmahi, Abdallah (IJRDO - Journal of Social Science and Humanities Research, 2024)
The research deals with a popular tale from the ancient Omani heritage. In our research, we tried to learn about the Omani heritage and the distinct Omani culture, especially its literary heritage.We dealt with the story with literary criticism and analysis, and we focused on the characters of the story, the method of narration, the language, the presentation, the quality of the wording, the artistic plot, the fertile imagination, and the idea that derived its roots from the Omani culture and imagination. In our research, we followed the descriptive and analytical approach that is consistent with the subject of the folk tale.